Puskin – újratöltve: Az intertextualitás problémája Tatyjana Tolsztaja Szüzsé című elbeszélése fordításának tükrében - Bagi, Ibolya (Studia Litteraria, 2020)
The paper analyses one of the short stories of Tatyana Tolstaya, who is one of the most important representatives of Russian postmodern literature. The study focuses on the loss in the translation process of intertextual connections when translated into another culture. In Tolstaya’s oeuvre the irony present in rich intertextual references and the grotesque and absurd methods primarily aim to de-pathos the classic Russian literature. The problem of intertextuality is most significant in Tolstaya’s “Szjuzset” therefore the difficulties of translation are most demonstrable in this work.